1992
DOI: 10.1042/bj2810137
|View full text |Cite
|
Sign up to set email alerts
|

Purification of an Arg-Gly-Asp selective matrix receptor from brain synaptic plasma membranes

Abstract: Brain synaptic plasma membranes specifically associated with matrix protein monolayers containing the Arg-Gly-Asp sequence recognized by integrin-type adhesion receptors. Experiments using fibronectin affinity chromatography to identify the synaptosomal receptors responsible for this interaction led to the purification of a 55 kDa Arg-Gly-Asp recognition protein that is labelled by antibodies against the alpha 5 beta 1 integrin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…2A). These observations support and extend previous studies that showed high expression of ␣5 integrin in pyramidal neurons in the hippocampus and in hippocampal synapses (21,22). Our results suggest that activity-induced changes at synapses promote ␣5 targeting to these sites, which is consistent with ␣5 signaling playing a regulatory role in synaptic function.…”
Section: Resultssupporting
confidence: 81%
“…2A). These observations support and extend previous studies that showed high expression of ␣5 integrin in pyramidal neurons in the hippocampus and in hippocampal synapses (21,22). Our results suggest that activity-induced changes at synapses promote ␣5 targeting to these sites, which is consistent with ␣5 signaling playing a regulatory role in synaptic function.…”
Section: Resultssupporting
confidence: 81%
“…Adhesion responses responsible for synaptic conformation likely are mediated by integrin-type matrix receptors found expressed in the adult brain and, in many instances, appropriately localized to synaptic contacts (Bahr and Lynch, 1992;Grooms et al, 1993;Einheber et al, 1996;Nishimura et al, 1998;Pinkstaff et al, 1998Pinkstaff et al, , 1999. In concordance with the physiology studies, matrix receptors purified from synaptic membranes adhere to matrix proteins via the RGDS integrin target sequence and respond to the same diverse pharmacological agents that influence LTP stabilization (Bahr and Lynch, 1992;Bahr et al, 1997;Capaldi et al, 1997).…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, the PSD-enriched PAC 1 glycoproteins (6, 7) have been identified as members of the cadherin family (8), providing evidence for such a role. Furthermore, integrin-type adhesion molecules (9) and NCAM (10), a member of the immunoglobulin (Ig) superfamily, have been recognized as SM components. Considering the complex interplay between stabilization and plasticity at synaptic connections, it is likely that more synaptic glycoproteins with adhesive functions are to be identified.…”
mentioning
confidence: 99%